Revisiting berberine for the prevention and treatment of Fusobacterium nucleatum-induced colorectal cancer from a dynamic perspective - Bi, Dongming; Yang, Xue; Yong, Jiangyan; Huang, Ju; Liu, Zhihao; Gong, Rui (Frontiers in Microbiology, 2025)
Colorectal Cancer (CRC), a common malignancy, often arises from adenomatous precursors. In the adenoma-carcinoma progression of CRC, Fusobacterium nucleatum (Fn) plays an important driving role. Therefore, the discovery of new drugs targeting Fn-induced disease progression is crucial for the prevention and treatment of CRC. Berberine (BBR), which has a relatively broad spectrum of antitumor activity, has received increasing attention in recent years. In this study, we summarize BBR's regulatory effects on the different stages of intestinal adenoma-carcinoma transformation induced by Fn and its anti-tumor mechanisms in the occurrence and development of CRC for the first time. Firstly, BBR can prevent the migration and intestinal colonization of Fn and regulate Fn-induced microbiota imbalance. Secondly, in the pre-cancerous lesion stage, BBR can attenuates Fn-mediated inflammation, inhibit abnormal crypt foci, and reverse adenoma progression. In addition, BBR can suppresses established CRC by inhibiting cell proliferation, invasion, metastasis, immune escape and drug resistance. For the classic pathogenic model of Fn-mediated CRC, the therapeutic effect of BBR is dynamic and comprehensive from pathogenic factors to pathological products. Among them, E-cadherin, Wnt/β-catenin, JAK/STAT and MAPK/ERK signaling pathways may be key to BBR's prevention of Fn-induced CRC.